Amazing stories of survival tales of hope, heroism & astaounding luck - Durkee, Cutler (People Books, 2006)
Collects forty-nine survival stories previously published in "People" magazine, including accounts of natural disasters, shipwrecks, animal attacks, hostage situations, medical miracles, terrorism, and war.